Utilizing SrSi2O2N2:Eu2+,Yb2+ phosphor to achieve high hue rendering index and high hue stability - Tung, Ha Thanh; Nguyen Thi, Dieu An (Institute of Advanced Engineering and Science, 2024)
For white-light emitting diode (WLED) applications, a green-to-orange emission nitridosilicate-based phosphor is created. The observed wide-band radiation in the green-orange range is caused by Eu2+ and Yb2+ at the trap point of a doubly doped SrSi2O2N2:Eu2+,Yb2+ (SSON:Eu,Yb) nitridosilicate phosphor. The green-color radiation’s decay duration was measured to validate the energy transfer among activator ions. The co-doping various ratios’ influence of activator ions on luminescence features was investigated. The resulting phosphor’s radiation is a function of the activator ion concentrations and raising the Yb2+ concentration causes red-color radiation to dominate the green radiation. To generate white illumination, the resulting phosphor was coupled with an InGaN blue-LED chip having a pumping wavelength of 450 nm. Two stages were taken to achieve hue balance management. Initially, the green to orange proportion was tuned by varying the Eu2+ and Yb2+ ions’ concentrations. At the second stage, the Commission Internationale de L’Eclairage, International Commission on Illumination (CIE) coordinates were changed from [0.2805; 0.2014] to [0.4071; 03789] by raising the amount of phosphor powder used. White illumination produced under optimal conditions has a hue rendering indicator of 89. The designed single-stage dual-hue-releasing nitridosilicate phosphor and blue-LED chip displayed remarkable hue steadiness over a wideband of forward-bias currents (100 to 500 mA at 3 V).